Clusterin expression in gastrointestinal neuroendocrine tumours is highly correlated with location and is helpful in determining the origin of liver metastases. Issue 5 (2nd September 2014) - Mourra, Najat; Scriva, Aurelie; Mansiaux, Yohann; Gozlan, Sarah; Bennis, Malika; Balaton, Andre
Abstract : Aims: Clusterin (CLU) is a sulphated glycoprotein implicated in many physiological and pathological processes, including tumorigenesis. We have previously demonstrated that CLU is highly expressed in pancreatic neuroendocrine tumours (NETs). The aims of this study were: to investigate CLU expression in gastrointestinal NETs; the potential correlation between this expression and different clinicopathological parameters; and its usefulness in the differential diagnosis of liver metastases. Methods and results: Immunohistochemistry using an anti‐CLU antibody was performed on paraffin sections from 108 primary NETs [G3 (13 cases), G2 (18 cases), and G1 (77 cases), according to the 2010 WHO classification] and 60 metastases. Cytoplasmic positivity was scored qualitatively and quantitatively. The pattern of staining was also assessed. Two‐step statistical analyses (univariate and multivariate logistic regression) were performed. More than 90% of small‐intestine NETs were completely negative. The probability of obtaining a positive CLU score was higher for the appendix, the stomach, the duodenum and the rectum than for the small intestine and colon. All G3 NETs and most G2 NETs were negative as compared with G1. CLU expression in the metastatic foci was identical to that of the primary tumour. Conclusions: Clusterin expression in gastrointestinal NETs is highly correlated with location and probably also with grading, in both the primary tumour and metastases. Underexpression of CLU in small‐intestine NETs is helpful for identifying the origin of liver metastases: a strong CLU score in a liver biopsy makes the small intestine highly unlikely as a primary site.